Assessment of mineral status in hilly and central dry zones of Karnataka and ways to supplement them - GOWDA, N K S; PRASAD, C S; RAMANA, J V; SHIVARAMAIAH, M T (The Indian Journal of Animal Sciences, 2014)
A study was undertaken to assess the mineral status of calcium (Ca), phosphorus (P), magnesium (Mg), copper (Cu), zinc (Zn) and iron (Fe) of soil, feeds/fodders and blood samples of animals in hilly and central dry zone of Kamataka. The extractable minerals from soil were within the creitical range in central dry zone, whereas, in hilly zone soil Ca (0.03%) and P (9 ppm) levels were below the criticalleyels. Paddy and ragi straw contained higher silica and were also lower in Ca, P, Cu and Zn than the critical levels. Cultivated green fodders and mixed local grasses in both the zones were moderate to good sources ofCa, Mg, Cu and were rich in Fe (206-2090 ppm). Legume fodders available in these zones contained good amo!1nt of Ca (1.8-2.4%), Cu (35-63 ppm), Zn (44-284 ppm) and Fe (652-2752 ppm). Fodder tree leaves like Erythrina, glyricidia, mulberry, and subabul contained higher levels of Ca (0.8-2.5%) followed by Cu, Zn and Fe. Cereal grains had lower ash content and were low in Mg (0.18%). Oilcakes and brans were good sources of P (1-2.96%). Certain unconventional feeds like gram hl,lsk, horse gram and groundnut haulms being fed to animals in these zones contained moderate to high levels of Zn (31-213 ppm), Fe (702-2901 ppm) and Ca (1.1-1.9%) but their bioavailability to the animals is yet to be seen. There existed some variation in the mineral content of feeds / fodders between the zones. Animals in hilly zone had significantly (P<0.01) lower P, Cu and Zn values in blood plasma and animals in central dry zone showed significantly (P<0.01) low Ca, Cu and Zn. Iron levels in animals of both the zones were within the normal range. Supplementation of green fodders, legumes, tree leaves along with concentrate ingredients like cakes and brans or alternatively providing region specifie mineral supplements could overcome the deficiency of minerals and could be a cost effective approach.